STRATEGI KOMUNIKASI PROGRAM RADIO TALK SHOW FAS @ KONATA DI RADIO KONATA SURAKARTA: STRATEGI KOMUNIKASI PROGRAM RADIO TALK SHOW FAS @ KONATA DI RADIO KONATA SURKARTA - Aji Wibisono, Bagas; Sarjono, Herning Suryo; Sihabuddin, Sihabuddin (Solidaritas, 2024)
The research aims to determine the communication strategy of the fas @ konata radio talk show program at radio konata surakarta with a research focus on communication strategies, radio konata, and the fas @ konata program. The limited means of communication media for children makes radio konata one of the media means for children to entertainment and education through radio broadcasts. The type of data and data sources in this research use descriptive qualitative using data collection techniques in the form of observation, interviews, documentation. The aspects examined in communication strategy based on the theory of communication strategy steps include : 1. Getting to know the audience, 2. Determining goals, 3. Developing messages, 4. Determining methods and choosing the media used. Overall, we get an overview of Konata Surakarta Radio's communication strategy to educate children through the Fas @ Konata program, namely : 1. Conducting roadshows to introduce the audience, conducting outdoor media publications and utilizing social media as a means of information and so on. 2. Establishing good relationship with broadcasters and listeners. 3. Presenting quality content, placing a different broadcast schedule at each time. 4. Utilizing technology to reach a wider audience through digital broadcasts and using Instagram social media as a means of information and so on.Keywords : Communication Strategy, Konata Radio and Fas @ Konata Program.